Description of stress-strain curves by three parameters - Ramberg, Walter (National Advisory Committee for Aeronautics, 1943)
A simple formula is suggested for describing the stress-strain curve in terms of three parameters: namely, Young's modulus and two secant yield strengths. Dimensionless charts are derived from this formula for determining the stress-strain curve, the tangent modulus, and the reduced modulus of a material for which these three parameters are given. Comparison with the tensile and compressive data on aluminum alloy, stainless-steel, and carbon-steel sheet in NACA Technical Note No. 840 indicates that the formula is adequate for most of these materials. The formula does not describe the behavior of alclade sheet, which shows a marked change in slope at low stress. It seems probable that more than three parameters will be necessary to represent such stress-strain curves adequately.
"July 1943."
NACA TN no. 902.
Keywords: Strains and stresses.; Mathematics -- Formulae.; elektronické knihy; electronic books